2008
DOI: 10.1211/ijpp.16.2.0003
|View full text |Cite
|
Sign up to set email alerts
|

Patient responses to an integrated service, initiated by community pharmacists, for the prevention of osteoporosis

Abstract: Objective This study aimed to develop, implement and evaluate an integrated service provided by pharmacists to consumers based on the results of a risk‐assessment survey carried out by the pharmacist and testing of bone mineral density (BMD) by a radiographer. It also investigated whether measurement of BMD in the pharmacy increased the effectiveness of the service and pharmacist referral in terms of adherence to advice and uptake of referral compared with the same service offered without BMD testing. Setting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(52 citation statements)
references
References 19 publications
1
50
0
1
Order By: Relevance
“…Tobacco users’ positive attitudes toward displaying quitting resources resonate with what has been observed in previous tobacco-related25 and other literature, such as osteoporosis counseling in community pharmacies 37…”
Section: Discussionsupporting
confidence: 66%
“…Tobacco users’ positive attitudes toward displaying quitting resources resonate with what has been observed in previous tobacco-related25 and other literature, such as osteoporosis counseling in community pharmacies 37…”
Section: Discussionsupporting
confidence: 66%
“…These specialised service models incorporate the idea of trained pharmacists providing pharmaceutical care or disease management through patient assessment, objective/subjective disease parameter testing, ongoing follow ups and collaboration with other health care providers. In the last decade, a plethora of innovative pharmacy-based services have been developed and tested and have demonstrated positive health outcomes in a variety of clinical areas including asthma, diabetes, cardiovascular disease and osteoporosis [2][3][4][5]. Concurrently, Australian pharmacy practice has also evolved, and complex, advanced community pharmacybased services models, demonstrating positive health outcomes, have now been developed and tested [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…These RCTs were conducted by various healthcare professionals such as primary care physicians,(53, 54) orthopaedic surgeons, (55,54) pharmacists (38)(39)(40) and nurses. (56).…”
Section: Discussionmentioning
confidence: 99%
“…Although, most pharmaceutical care services are mainly targeted at treatment of osteoporosis. A further literature search revealed that there are three randomized control trials (RCTs) conducted by community pharmacies in Canada, Australia and US to evaluate the impact of pharmacist's interventions on osteoporosis management (38)(39)(40). However, two of these studies were considered biased (41).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation